If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + -1)(5x + -1) = 7 Reorder the terms: (-1 + 5x)(5x + -1) = 7 Reorder the terms: (-1 + 5x)(-1 + 5x) = 7 Multiply (-1 + 5x) * (-1 + 5x) (-1(-1 + 5x) + 5x * (-1 + 5x)) = 7 ((-1 * -1 + 5x * -1) + 5x * (-1 + 5x)) = 7 ((1 + -5x) + 5x * (-1 + 5x)) = 7 (1 + -5x + (-1 * 5x + 5x * 5x)) = 7 (1 + -5x + (-5x + 25x2)) = 7 Combine like terms: -5x + -5x = -10x (1 + -10x + 25x2) = 7 Solving 1 + -10x + 25x2 = 7 Solving for variable 'x'. Reorder the terms: 1 + -7 + -10x + 25x2 = 7 + -7 Combine like terms: 1 + -7 = -6 -6 + -10x + 25x2 = 7 + -7 Combine like terms: 7 + -7 = 0 -6 + -10x + 25x2 = 0 Begin completing the square. Divide all terms by 25 the coefficient of the squared term: Divide each side by '25'. -0.24 + -0.4x + x2 = 0 Move the constant term to the right: Add '0.24' to each side of the equation. -0.24 + -0.4x + 0.24 + x2 = 0 + 0.24 Reorder the terms: -0.24 + 0.24 + -0.4x + x2 = 0 + 0.24 Combine like terms: -0.24 + 0.24 = 0.00 0.00 + -0.4x + x2 = 0 + 0.24 -0.4x + x2 = 0 + 0.24 Combine like terms: 0 + 0.24 = 0.24 -0.4x + x2 = 0.24 The x term is -0.4x. Take half its coefficient (-0.2). Square it (0.04) and add it to both sides. Add '0.04' to each side of the equation. -0.4x + 0.04 + x2 = 0.24 + 0.04 Reorder the terms: 0.04 + -0.4x + x2 = 0.24 + 0.04 Combine like terms: 0.24 + 0.04 = 0.28 0.04 + -0.4x + x2 = 0.28 Factor a perfect square on the left side: (x + -0.2)(x + -0.2) = 0.28 Calculate the square root of the right side: 0.529150262 Break this problem into two subproblems by setting (x + -0.2) equal to 0.529150262 and -0.529150262.Subproblem 1
x + -0.2 = 0.529150262 Simplifying x + -0.2 = 0.529150262 Reorder the terms: -0.2 + x = 0.529150262 Solving -0.2 + x = 0.529150262 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.2' to each side of the equation. -0.2 + 0.2 + x = 0.529150262 + 0.2 Combine like terms: -0.2 + 0.2 = 0.0 0.0 + x = 0.529150262 + 0.2 x = 0.529150262 + 0.2 Combine like terms: 0.529150262 + 0.2 = 0.729150262 x = 0.729150262 Simplifying x = 0.729150262Subproblem 2
x + -0.2 = -0.529150262 Simplifying x + -0.2 = -0.529150262 Reorder the terms: -0.2 + x = -0.529150262 Solving -0.2 + x = -0.529150262 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.2' to each side of the equation. -0.2 + 0.2 + x = -0.529150262 + 0.2 Combine like terms: -0.2 + 0.2 = 0.0 0.0 + x = -0.529150262 + 0.2 x = -0.529150262 + 0.2 Combine like terms: -0.529150262 + 0.2 = -0.329150262 x = -0.329150262 Simplifying x = -0.329150262Solution
The solution to the problem is based on the solutions from the subproblems. x = {0.729150262, -0.329150262}
| 9x^2=24x-16 | | (1/4)(2x+6)=4x | | 38=(x+3)+(x+9)+(x^2-2x)+(3x-2) | | x(7x+22)+16=0 | | 2x^2-7+13x=0 | | 9x+8=6x+11 | | 8n+11n-6=7n+34-4n | | (1/6)(2x+64)=3x | | 45x^3+105x^2+50x=0 | | 3x-27=54+12x | | 30+11x+x^2=0 | | 110x^2+21x-110=0 | | 5a+5(1)=9 | | 180n-360=(n-2)180 | | u^2-16u+10=0 | | 4y+7=2x-21 | | H=WQx | | a^2-9ab+14b^2=0 | | 8.45+3.3+6= | | 9c^2-10c+1=0 | | 8x+5y-z=0 | | x+3x+6x-6=180 | | 4x=3+8 | | 4(x-4)=4x+32 | | 35x^2+93x+54=0 | | -4x+7y=27 | | 3(x+3)+3=-15(x+2) | | -7x-14-14=5x | | 35x^2+83x+54=0 | | log(3)(x+16)-log(3)(x-10)=3 | | 4x+5y=-19 | | 2a^2-9a=0 |